Penyuluhan Cara Bijak Menggunakan Media Sosial untuk Generasi Muda - Zoni Sulaiman; Asep Nurjamin; Didin Sahidin; Cecep Dudung Julianto; Alawi Fauzi (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
Social media is a very important part of the life of modern society. Even though it is not a basic need, in this era, activities in social media have become an almost routine part of people from various backgrounds. The younger generation as part of society that is most responsive to technological advances has a high intensity in using social media. However, the level of thinking maturity of the younger generation who is still in the process of development often makes them less wise in using social media. Therefore, this community service activity aims to provide counseling to the younger generation to be wiser in responding to various issues that develop on social media, and can respond to them with smart steps. This community service activity is expected to provide benefits in the form of reducing social cases caused by the behavior of using social media that is not wise.